Integrated mRNA and miRNA transcriptome analysis of grape in responses to salt stress - Wei, Lingzhu; Du, Yuanpeng; Xiang, Jiang; Zheng, Ting; Cheng, Jianhui; Wu, Jiang (Frontiers in Plant Science, 2023)
Salt stress is an important factor which may negatively affect plant growth and development. High concentrations of Na+ ions can destroy the ion balance in plant somatic cells, as well as destroying cell membranes and forming a large number of reactive oxygen species (ROS) and other damage mechanisms. However, plants have evolved numerous defense mechanisms in response to the damages caused by salt stress conditions. Grape (Vitis vinifera L.), a type of economic crop, is widely planted throughout the world. It has been found that salt stress is an important factor affecting the quality and growth of grape crops. In this study, a high-throughput sequencing method was used to identify the differentially expressed miRNAs and mRNAs in grapes as responses to salt stress. A total of 7,856 differentially expressed genes under the salt stress conditions were successfully identified, of which 3,504 genes were observed to have up-regulated expressions and 4,352 genes had down-regulated expressions. In addition, this study also identified 3,027 miRNAs from the sequencing data using bowtie and mireap software. Among those, 174 were found to be highly conserved, and the remaining miRNAs were less conserved. In order to analyze the expression levels of those miRNAs under salt stress conditions, a TPM algorithm and DESeq software were utilized to screen the differentially expressed miRNAs among different treatments. Subsequently, a total of thirty-nine differentially expressed miRNAs were identified, of which fourteen were observed to be up-regulated miRNAs and twenty-five were down-regulated under the salt stress conditions. A regulatory network was built in order to examine the responses of grape plants to salt stress, with the goal of laying a solid foundation for revealing the molecular mechanism of grape in responses to salt stress.